High-performance zinc alloy with gradient structure and preparation method and application thereof
By designing grain gradient structure and nano-precipitation phase in zinc alloy, the problem of insufficient corrosion resistance of zinc alloy is solved, and the application of high-performance zinc alloy in biomedical implant devices is realized, with excellent mechanical properties and biocompatibility.
Patent Information
- Application Number
- CN202511304763.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-12
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-09-12
AI Technical Summary
Traditional zinc alloys have deficiencies in corrosion resistance and are difficult to meet the requirements of biomedical implant devices. Existing alloying and surface treatment methods have problems such as high production costs, complex processes, and difficulty in maintaining mechanical properties and biocompatibility.
By controlling the grain size of the Zn-0.4Mn alloy to present a gradient distribution of "fine→coarse→fine", and combining ultrasonic compression and heat treatment processes, a nano-precipitated phase is formed, a grain gradient structure is achieved, and the corrosion resistance and mechanical properties of the zinc alloy are improved.
It significantly improves the deformation resistance, thermomechanical stability and corrosion resistance of zinc alloys, making them particularly suitable for biomedical implants such as vascular stents and bone nails, with excellent tensile strength and elongation.
Smart Images

Figure CN120796778A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a high-performance zinc alloy with a gradient structure and its preparation method and application, belonging to the technical field of metal material processing. BACKGROUND
[0002] Zinc alloy, as an important metal material, has a wide range of applications in various industries. However, traditional zinc alloys have obvious shortcomings in terms of corrosion resistance, which limits their promotion in high-end application fields, especially in biomedical implant devices. Biomedical implant devices require materials not only to have good mechanical properties and biocompatibility, but also to have excellent corrosion resistance to ensure the long-term stability and safety of the device in the body.
[0003] Currently, alloying (adding Al, Cu, Mg, Mn, etc.) and surface treatment (electroplating, chemical plating, anodic oxidation, etc.) can effectively improve the corrosion resistance of zinc alloys. However, both methods have significant drawbacks: for alloying, the type and content of alloying elements need to be precisely controlled, otherwise it may adversely affect the mechanical properties and processing performance of the alloy. And alloying often needs long-time diffusion treatment at high temperature, which increases the production cost and processing difficulty. For surface treatment: these surface treatment techniques are often complex, and it is difficult to maintain good mechanical properties and biocompatibility while ensuring corrosion resistance. In addition, the surface protective film may be damaged due to wear, scratches, etc. during use, resulting in a decrease in corrosion resistance.
[0004] In recent years, with the continuous development of material science and preparation technology, gradient structure materials have attracted much attention due to their unique performance advantages. By precisely controlling the gradient structure of materials, their performance can be optimized and controlled. However, there are relatively few studies on the application of gradient structure to zinc alloys to improve their corrosion resistance.
[0005] Therefore, it is of great significance to develop a new type of zinc alloy with high corrosion resistance and easy processing and its preparation method. The present application realizes the gradient distribution of zinc alloy grain size by precisely controlling the alloy composition, heat treatment process and ultrasonic compression parameters, thereby significantly improving its corrosion resistance. This high-performance zinc alloy with a gradient structure not only has good mechanical properties and biocompatibility, but is also particularly suitable for high-end application fields such as biomedical implant devices. SUMMARY
[0006] The present application provides a high-performance zinc alloy with a gradient structure, which not only has good mechanical properties and biocompatibility, but is also particularly suitable for high-end application fields such as biomedical implant devices.
[0007] Meanwhile, the application provides a preparation method of the high-performance zinc alloy with the gradient structure.
[0008] Meanwhile, the application provides an application of the high-performance zinc alloy with the gradient structure.
[0009] To solve the above technical problems, the application adopts the technical scheme of: The high-performance zinc alloy with the gradient structure is Zn-0.4Mn alloy in a cast state, and the grain size of the alloy from top to center to bottom is in a distribution of fine to coarse to fine, wherein the grain size of the edge area (top / bottom) is less than or equal to 2 microns, the grain size of the center area is 5-20 microns, and the grain size of the transition area between the edge and the center is 2-15 microns. Meanwhile, all the areas are accompanied by nanometer precipitated phases with a size less than or equal to 50 nm.
[0010] In the Zn-0.4Mn alloy, 0.4wt% of Mn and the balance of Zn are included.
[0011] In the application, preferably, the thickness of the transition area of the gradient structure is 10-30% of the height of the compression sample. The nanometer precipitated phase is MnZn 13 , and the area fraction is 3-15% (calculated by ImagePro software).
[0012] The preparation method of the high-performance zinc alloy with the gradient structure comprises the following steps: S1, placing the cast Zn-0.4Mn alloy in a heat treatment furnace for homogenization treatment, the heat treatment temperature is 300-350 DEG C, the holding time is 4-6 hours, and after the holding ends, water cooling is performed to obtain a homogenized alloy; S2, placing the homogenized zinc alloy obtained in S1 in a graphite clamp of a high-frequency electromagnetic induction heating device, ensuring that only the core area (axial height 30%-60%) of the alloy is in the effective heating area of the electromagnetic induction heating, starting the high-frequency induction power supply to rapidly heat the target area of the core of the alloy. Meanwhile, an infrared thermal imaging thermometer is used to measure the temperature of the alloy in real time, and when the temperature of the core reaches 150-250 DEG C, the induction heating is immediately stopped to obtain the alloy with a temperature gradient. After completion, the alloy is quickly (<15s) placed in a compression mold of an ultrasonic plastic welding machine processing platform; The method for ensuring that only the core area of the alloy is in the effective heating area of the electromagnetic induction heating is to control the size of the induction coil (for example, if the size of the core area is 5 mm, the diameter / width of the induction coil is about 3 mm).
[0013] S3, by hydraulic system to apply 5-50MPa axial pressure, while applying frequency 15-25kHz, amplitude 5-50um ultrasonic vibration, compression amount reaches 30% when stop processing; S4, the alloy obtained in S3 is turned upside down by 180°, and the steps of S2 and S3 are repeated, and the cumulative compression amount reaches 60% when stop processing.
[0014] S5, the alloy obtained in S4 is placed in a heat treatment furnace, and short-term aging treatment is carried out at 250-350℃ for 0.2-2 hours, and air cooling is carried out after the end, to obtain the final alloy.
[0015] In the application, preferably, the pressure head of the ultrasonic plastic welding machine is made of TC4 titanium alloy, the contact surface is a plane with a diameter of 10-50mm, and the working end surface hardness is greater than or equal to HRC50.
[0016] In the application, preferably, in S1, the as-cast Zn-0.4Mn alloy is a cylinder with a height-diameter ratio of (1.2-1.5):1, wherein the diameter is 5-10mm, and the height is 6-15mm.
[0017] In the application, preferably, in S2, the working frequency of the high-frequency electromagnetic induction heating device is 20-50kHz.
[0018] The alloy obtained by the application has an overall elastic modulus of at least 125GPa, a tensile strength of 256-288MPa, an elongation of 42-54%, and an edge area corrosion current density of 0.1×10 -7 -0.5×10 -7 A / cm 2 , and a center area corrosion current density of 1.50×10 -7 -2.00×10 -7 A / cm 2 .
[0019] The application of the high-performance zinc alloy with a gradient structure in the biological medical implant device is particularly suitable for blood vessel stents, bone nails and the like.
[0020] Compared with the prior art, the application has the following beneficial effects: The application realizes synchronous improvement of strength and plasticity by the "fine-coarse-fine" grain gradient design, the edge nanocrystalline layer (≤2um) provides high strength, the center coarse grain area (5-20um) maintains good plasticity, the overall tensile strength and elongation can reach more than 250MPa and 40%, and the gradient change of the transition area (2-15um) effectively relieves the interface stress concentration.
[0021] The elastic modulus of the Zn-0.4Mn alloy prepared by the method reaches at least 125 GPa, and the alloy has excellent deformation resistance and thermal mechanical stability.
[0022] The fine grains in the edge region form a dense grain boundary network, hinder the penetration of corrosive medium, and make the corrosion current density as low as 0.1*10 -7 A / cm 2 The gradient structure makes the edge region have slightly higher corrosion resistance than the center region, and the alloy is particularly suitable for high-end application fields such as vascular stents, bone nails and other biomedical implant devices.
[0023] The ultrasonic vibration compression method has the advantages of simple processing mode, high efficiency, high precision, small heat input, no pollution and low cost, and has a wide application prospect.
[0024] The present application relates to a high-performance zinc alloy with a gradient structure and a preparation method and application thereof, and belongs to the technical field of metal material processing. The zinc alloy adopts a Zn-0.4Mn as-cast alloy, and through specific heat treatment and ultrasonic compression process, a microstructure with a grain size gradient distribution of "fine-> coarse-> fine" from top to bottom is formed, the grain size in the edge region is ≤2μm, the grain size in the center region is 5-20μm, the grain size in the transition region is 2-15μm, and a nano precipitated phase (MnZn 13 ) with a size of ≤50nm is accompanied. The alloy has excellent deformation resistance and thermal mechanical stability, and the elastic modulus thereof can reach at least 125 GPa. At the same time, the alloy also has excellent corrosion resistance, the corrosion current density in the edge region is 0.1*10 -7 -0.5*10 -7 A / cm 2 , the corrosion current density in the center region is 1.50*10 -7 -2.00*10 -7 A / cm 2 , and the alloy is particularly suitable for biomedical implant devices such as vascular stents, bone nails and the like. BRIEF DESCRIPTION OF DRAWINGS
[0025] Figure 1 Fig. 1 is an IPF map of the edge region of the gradient Zn-0.4Mn alloy of Example 1 of the present application, showing a microstructure with an average grain size of 1.57μm; Figure 2 Fig. 2 is an IPF map of the center region of the gradient Zn-0.4Mn alloy of Example 1 of the present application, showing a microstructure with an average grain size of 12.83μm.
[0026] Figure 3 Fig. 3 is a TEM image of the grain interior of the Zn-0.4Mn alloy of Example 1 of the present application, showing a nano precipitated phase (dark gray dots) with a size of ≤50nm. DETAILED DESCRIPTION
[0027] The following will be further described in conjunction with the accompanying drawings and the contents of the embodiments of the present invention to make the purpose, technical solutions and advantages of the present invention clearer. The specific embodiments described are only used to explain the present invention and are not used to limit the present invention. Example 1
[0028] A high-performance zinc alloy with a gradient structure, wherein the alloy used is a cast Zn-0.4Mn alloy, and the grain size of the alloy is distributed in the order of "fine → coarse → fine" from "upper → middle → lower". Figure 1 As shown, the average grain size of the edge region (upper / lower) is 1.57 μm. Figure 2 As shown in the figure, the average grain size in the center is 12.83 μm, and the grain size in the transition area between the edge and the center is 2 to 10 μm (transition from 2 μm to 10 μm). Figure 3 As shown in Figure 1, all regions are accompanied by nano-precipitated phases with a size of ≤50nm. In this embodiment, the thickness of the transition region of the gradient structure is 20% of the height of the compressed sample (final compressed sample). The nano-precipitated phase is MnZn 13 , the volume fraction is 10%.
[0029] A method for preparing a high-performance zinc alloy with a gradient structure comprises the following steps: S1, a cylinder of as-cast Zn-0.4Mn alloy with a height-to-diameter ratio of 1.2:1, wherein the diameter of the as-cast Zn-0.4Mn alloy is 5 mm and the height of the as-cast Zn-0.4Mn alloy is 6 mm; the as-cast Zn-0.4Mn alloy is placed in a heat treatment furnace for homogenization treatment at a heat treatment temperature of 325°C for a holding time of 5 hours, and then water-cooled after the holding period to obtain a homogenized alloy.
[0030] In step S2, the homogenized zinc alloy obtained in step S1 is placed in the graphite fixture of a high-frequency electromagnetic induction heating device, ensuring that only the core region of the alloy (ranging from 30% to 60% of the axial height) is within the effective heating zone of the electromagnetic induction heating. The high-frequency induction power supply is activated to rapidly heat the target core region of the alloy. Specifically, the operating frequency of the high-frequency electromagnetic induction heating device is 35 kHz. Simultaneously, the alloy is measured in real time using an infrared thermal imaging thermometer. When the core temperature reaches 200°C, the induction heating is immediately stopped, resulting in an alloy with a temperature gradient. After completion, the alloy is quickly (<15 seconds) placed in the compression mold of the ultrasonic plastic welder processing platform. The indenter of the ultrasonic plastic welder is made of TC4 titanium alloy, with a flat contact surface of 10 mm in diameter and a working end hardness ≥ HRC50.
[0031] The method to ensure that only the core area of the alloy is in the effective heating area of electromagnetic induction heating is to control the size of the induction coil (for example, if the core area size is 5mm, then the diameter / width of the induction coil is about 3mm).
[0032] S3, applying 30 MPa axial pressure through the hydraulic system and simultaneously applying ultrasonic vibration with a frequency of 20 kHz and an amplitude of 30 μm, and stopping the processing when the compression reaches 30%; In step S4, the alloy obtained in step S3 is turned upside down 180°, and steps S2 and S3 are repeated. The processing is stopped when the cumulative compression reaches 60%.
[0033] S5, placing the alloy obtained in S4 in a heat treatment furnace, performing a short-time aging treatment at 300°C for 1 hour, and then air-cooling to obtain a final alloy.
[0034] The application of a high-performance zinc alloy with a gradient structure in this embodiment in biomedical implant devices is particularly suitable for vascular stents, bone nails, etc. Example 2
[0035] A high-performance zinc alloy with a gradient structure, the alloy used in the cast state is Zn-0.4Mn alloy, the alloy's "up → middle → bottom" grain size is distributed in a "fine → coarse → fine" manner, wherein the average grain size of the edge area (upper / lower) is 2μm, the average grain size of the central area is 20μm, and the grain size of the transition area between the edge and the center is 2 to 15μm (transition from 2μm to 15μm). At the same time, all areas are accompanied by nano-precipitates with a size of ≤50nm. In this embodiment, the thickness of the transition area of the gradient structure is 30% of the height of the compressed sample (final compressed sample). The nano-precipitates are MnZn 13 , volume fraction 15%.
[0036] A method for preparing a high-performance zinc alloy with a gradient structure comprises the following steps: S1, a cylinder of as-cast Zn-0.4Mn alloy with a height-to-diameter ratio of 1.5:1, wherein the diameter of the as-cast Zn-0.4Mn alloy is 10 mm and the height of the as-cast Zn-0.4Mn alloy is 15 mm; the as-cast Zn-0.4Mn alloy is placed in a heat treatment furnace for homogenization treatment at a heat treatment temperature of 350° C. for a holding time of 6 hours, and then water-cooled after the holding period to obtain a homogenized alloy.
[0037] S2, the homogenized zinc alloy obtained in S1 is placed in a graphite clamp of a high-frequency electromagnetic induction heating device, ensuring that only the core region (axial height 30%~60%) of the alloy is in the effective heating zone of electromagnetic induction heating. Start the high-frequency induction power supply to quickly heat the target region of the core of the alloy. Specifically, the working frequency of the high-frequency electromagnetic induction heating device is 50 kHz. At the same time, use an infrared thermal imaging thermometer to measure the temperature of the alloy in real time, and stop the induction heating immediately when the core temperature reaches 250℃. An alloy with a temperature gradient is obtained. After completion, quickly (<15s) place it in the compression mold of the ultrasonic plastic welding machine processing platform; the pressure head of the ultrasonic plastic welding machine is made of TC4 titanium alloy, and the contact surface is a flat surface with a diameter of 50mm, and the working end surface hardness is ≥HRC50.
[0038] The method for ensuring that only the core region of the alloy is in the effective heating zone of electromagnetic induction heating is to control the size of the induction coil (for example, if the core region size is 5mm, then the diameter / width of the induction coil is about 3mm).
[0039] S3, apply 50MPa axial pressure through the hydraulic system, while applying ultrasonic vibration with a frequency of 25kHz and an amplitude of 50μm, stop processing when the compression amount reaches 30%; S4, flip the alloy obtained in S3 upside down by 180°, repeat the steps of S2 and S3, and stop processing when the cumulative compression amount reaches 60%.
[0040] S5, place the alloy obtained in S4 in a heat treatment furnace and perform short-term aging treatment at 350℃ for 2 hours, and then air cool to obtain the final alloy.
[0041] The application of the high-performance zinc alloy with a gradient structure in the biological medical implant device is particularly suitable for vascular stents, bone nails, etc. Example 3
[0042] A high-performance zinc alloy with a gradient structure, the as-cast alloy used is Zn-0.4Mn alloy, and the "top→middle→bottom" grain size of the alloy shows a "fine→coarse→fine" distribution, wherein the average grain size of the edge region (top / bottom) is 1.0μm, the average grain size of the center region is 5μm, and the grain size of the transition region between the edge and the center is 2~5μm (transition from 2μm to 5μm). At the same time, all regions are accompanied by nano precipitates with a size of ≤50nm. In this embodiment, the thickness of the transition region of the gradient structure is 10% of the height of the compression sample (the final compression sample). The nano precipitates are MnZn 13 with a volume fraction of 3%.
[0043] A method for preparing a high-performance zinc alloy with a gradient structure, comprising the following steps: S1, a cylinder of as-cast Zn-0.4Mn alloy with a height-to-diameter ratio of 1.5:1, wherein the diameter of the as-cast Zn-0.4Mn alloy is 10 mm and the height of the as-cast Zn-0.4Mn alloy is 15 mm; the as-cast Zn-0.4Mn alloy is placed in a heat treatment furnace for homogenization treatment at a heat treatment temperature of 300°C for a holding time of 4 hours, and then water-cooled to obtain a homogenized alloy.
[0044] In step S2, the homogenized zinc alloy obtained in step S1 is placed in the graphite fixture of a high-frequency electromagnetic induction heating device, ensuring that only the core region of the alloy (ranging from 30% to 60% of the axial height) is within the effective heating zone of the electromagnetic induction heating. The high-frequency induction power supply is activated to rapidly heat the target core region of the alloy. Specifically, the operating frequency of the high-frequency electromagnetic induction heating device is 20 kHz. Simultaneously, the alloy is measured in real time using an infrared thermal imaging thermometer. When the core temperature reaches 150°C, the induction heating is immediately stopped, resulting in an alloy with a temperature gradient. After completion, the alloy is quickly (<15 seconds) placed in the compression mold of the ultrasonic plastic welder processing platform. The indenter of the ultrasonic plastic welder is made of TC4 titanium alloy, with a flat contact surface of 30 mm in diameter and a working end hardness ≥ HRC50.
[0045] The method to ensure that only the core area of the alloy is in the effective heating area of electromagnetic induction heating is to control the size of the induction coil (for example, if the core area size is 5mm, then the diameter / width of the induction coil is about 3mm).
[0046] S3, applying 5 MPa axial pressure through the hydraulic system and simultaneously applying ultrasonic vibration with a frequency of 15 kHz and an amplitude of 5 μm, and stopping the processing when the compression reaches 30%; In step S4, the alloy obtained in step S3 is turned upside down 180°, and steps S2 and S3 are repeated. The processing is stopped when the cumulative compression reaches 60%.
[0047] S5, placing the alloy obtained in S4 in a heat treatment furnace, performing a short-time aging treatment at 250°C for 0.2 hours, and then air-cooling to obtain a final alloy.
[0048] The application of a high-performance zinc alloy with a gradient structure in this embodiment in biomedical implant devices is particularly suitable for vascular stents, bone nails, etc. Example 4
[0049] The difference between this embodiment and embodiment 1 is that: In S2, when the core temperature reaches 180°C, the induction heating is immediately stopped. Example 5
[0050] The difference between this embodiment and embodiment 1 is that: S3, 40 MPa axial pressure is applied by the hydraulic system, while ultrasonic vibration with a frequency of 18 kHz and an amplitude of 20 pm is applied, and the processing is stopped when the compression amount reaches 30%.
[0051] Comparative Example 1
[0052] The difference between this comparative example and Example 1 is only that S2 is replaced by: S2, the homogenized zinc alloy obtained in S1 is heated again in a heat treatment furnace, the heating temperature is 200°C, the heating time is 0.5 hours, after heating, a uniform room temperature water is sprayed on the surface of the alloy using a water mist spray bottle and is placed for 60s, so that a temperature gradient is formed on the surface and inside of the alloy, and then the alloy is quickly placed in the compression mold of the ultrasonic plastic welding machine processing platform.
[0053] Comparative Example 2
[0054] The difference between this comparative example and Example 1 is only that ultrasonic vibration is not applied during compression.
[0055] Specifically, S3, 30 MPa axial pressure is applied by the hydraulic system, and the processing is stopped when the compression amount reaches 30%; S4, the alloy obtained in S3 is flipped upside down by 180°, the steps of S2 and S3 are repeated, and the processing is stopped when the cumulative compression amount reaches 60%.
[0056] Comparative Example 3
[0057] The difference between this comparative example and Example 1 is only that the frequency and amplitude of the ultrasonic vibration applied during compression are smaller.
[0058] Specifically, S3, 30 MPa axial pressure is applied by the hydraulic system, while ultrasonic vibration with a frequency of 10 kHz and an amplitude of 3 pm is applied, and the processing is stopped when the compression amount reaches 30%; S4, the alloy obtained in S3 is flipped upside down by 180°, the steps of S2 and S3 are repeated, and the processing is stopped when the cumulative compression amount reaches 60%.
[0059] Comparative Example 4
[0060] The difference between this comparative example and Example 1 is only that the frequency and amplitude of the ultrasonic vibration applied during compression are larger.
[0061] Specifically, S3, 30 MPa axial pressure is applied by the hydraulic system, while ultrasonic vibration with a frequency of 30 kHz and an amplitude of 60 pm is applied, and the processing is stopped when the compression amount reaches 30%; S4, the alloy obtained in S3 is flipped upside down by 180°, the steps of S2 and S3 are repeated, and the processing is stopped when the cumulative compression amount reaches 60%.
[0062] Comparative Example 5
[0063] The difference between the present comparative example and Example 1 is that the cumulative compression amount is slightly small.
[0064] Specifically, S4, the alloy obtained in S3 is turned upside down by 180°, and the steps of S2 and S3 are repeated, and the processing is stopped when the cumulative compression amount reaches 55%.
[0065] Comparative Example 6
[0066] The difference between the present comparative example and Example 1 is that the cumulative compression amount is slightly large.
[0067] Specifically, S4, the alloy obtained in S3 is turned upside down by 180°, and the steps of S2 and S3 are repeated, and the processing is stopped when the cumulative compression amount reaches 65%.
[0068] The performance parameters of the examples and comparative examples of the present application are shown in Table 1 below.
[0069] Table 1
[0070] In the present application, the elastic modulus is obtained by nanoindentation experiment, and the relevant test standard is GB / T 22458-2008.
[0071] The edge and central area corrosion current is measured in Hank's solution at 37±0.5℃ (the reference electrode is saturated calomel electrode), and the relevant test standard is GB / T 24196-2009.
[0072] The relevant test standard of elongation and tensile strength is GB / T 22458-2008.
[0073] It should be understood that, in order to simplify the present disclosure and to help in understanding one or more of the various inventive aspects, various features of the present application have sometimes been grouped together in a single embodiment, figure, or description of an embodiment discussed above. However, the method of this disclosure should not be interpreted to reflect an intention that the claimed application requires more features than are explicitly recited in each claim. Rather, as is reflected in the claims, inventive aspects lie in fewer than all features of the above-disclosed embodiments. Accordingly, the claims that follow the detailed description are hereby expressly incorporated into this detailed description, with each claim standing on its own as a separate embodiment of this application.
[0074] While the application has been described in accordance with the various embodiments shown and described, one of ordinary skill in the art will readily recognize that there could be variations made to the application without departing from the scope of the application. Accordingly, many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the application. Accordingly, the specification is to be regarded in an illustrative rather than a restrictive sense, and all such modifications are intended to be included within the scope of the application.
[0075] The above description is only the preferred embodiment of the present application, it should be pointed out that for those of ordinary skill in the art, several improvements and refinements can be made without departing from the principles of the present application, and these improvements and refinements should be considered as the protection scope of the present application.
Claims
1. A high-performance zinc alloy with a gradient structure, characterized by: The grain size of the alloy is distributed from fine to coarse to fine in the upper, middle and lower regions. The grain size of the upper and lower regions is ≤2μm, the grain size of the central region is 5-20μm, and the grain size of the transition region between the upper and lower regions and the central region is 2-15μm. At the same time, all regions are accompanied by MnZn with a size of ≤50nm. 13 Nanoprecipitated phase.
2. The high-performance zinc alloy with a gradient structure according to claim 1, characterized in that: The alloy is a cast Zn-0.4Mn alloy.
3. The high-performance zinc alloy with a gradient structure according to claim 1, characterized in that: The thickness of the transition zone is 10 to 30% of the height of the alloy compression specimen.
4. The high performance zinc alloy with a gradient structure according to claim 1, characterized in that: The overall elastic modulus of the alloy is at least 125 GPa, the tensile strength is 256~288 MPa, the elongation is 42~54%, and the corrosion current density in the upper and lower regions is 0.1×10 -7 ~0.5×10 -7 A / cm 2 The corrosion current density in the central area is 1.50×10 -7 ~2.00×10 -7 A / cm 2 .
5. The method for preparing a high-performance zinc alloy with a gradient structure according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, placing the as-cast Zn-0.4Mn alloy in a heat treatment furnace for homogenization treatment at a temperature of 300° C. to 350° C. for a holding time of 4 to 6 hours, and then water cooling to obtain a homogenized alloy; S2, placing the homogenized alloy obtained in S1 in a graphite fixture of a high-frequency electromagnetic induction heating device, ensuring that only the core region of the alloy is within the effective heating zone of the electromagnetic induction heating; starting the high-frequency induction power supply to rapidly heat the core region of the alloy; simultaneously, using an infrared thermal imaging thermometer to measure the temperature of the alloy in real time, and immediately stopping the induction heating when the temperature of the core region reaches 150°C to 250°C to obtain an alloy with a temperature gradient; after completion, quickly placing it in a compression mold on the processing platform of an ultrasonic plastic welder within less than 15 seconds; S3, applying 5-50 MPa axial pressure through the hydraulic system of the compression mold, and simultaneously applying ultrasonic vibration with a frequency of 15-25 kHz and an amplitude of 5-50 μm, and stopping the processing when the compression reaches 30%; S4, turning the alloy obtained in S3 upside down 180°, repeating steps S2 and S3, and stopping the processing when the cumulative compression reaches 60%; S5, placing the alloy obtained in S4 in a heat treatment furnace, performing a short-time aging treatment at 250°C to 350°C for 0.2 to 2 hours, and then air-cooling to obtain a final alloy.
6. The preparation method according to claim 5, characterized in that: In S1, the cast Zn-0.4Mn alloy is a cylinder with a height-to-diameter ratio of (1.2-1.5):1, wherein the diameter is 5-10 mm and the height is 6-15 mm.
7. The preparation method according to claim 5, characterized in that: In S2, the core region is in the range of 30% to 60% of the axial height of the homogenized alloy.
8. The preparation method according to claim 5, characterized in that: In S2, the operating frequency of the high-frequency electromagnetic induction heating device is 20 to 50 kHz.
9. The preparation method according to claim 5, characterized in that: In S2, the pressure head of the ultrasonic plastic welder is made of TC4 titanium alloy, the contact surface is a plane with a diameter of 10 to 50 mm, and the hardness of the working end surface is ≥HRC50.
10. Use of a high-performance zinc alloy with a gradient structure according to any one of claims 1 to 4 in biomedical implant devices, characterized in that: Biomedical implants include vascular stents and bone screws.
Citation Information
Patent Citations
High-strength high-ductility biodegradable Zn-Mn-Mg series zinc alloy and preparation method thereof
CN108588484A
Zinc-based alloy sheet for construction and preparation method thereof
CN109536779A
Method for double refining primary phases in zinc alloy
CN111101021A
Preparation method and application of high-strength and high-plasticity Zn-Mn alloy with core-shell structure
CN118028659A
Anti-aging plastic-extension high-performance zinc alloy as well as preparation method and application thereof
CN119332134A
Cited By
Nanocrystalline zinc alloy with high hardness and high modulus as well as preparation method and application of nanocrystalline zinc alloy
CN121780936A
A nanocrystalline zinc alloy with high hardness and high modulus, and a preparation method and application thereof
CN121780936B
